ANALYSIS OF PATIENT’S EXPECTATION AND SATISFACTION IN THE CLINIC FOR ASTHMA-ALLERGY OF DR. INDRAJANA JAKARTA - Siti Zulaiha Umi Difinubun (UHAMKA Press, 2017)
Background: Today, Community healthcare requires provider’s reliability in order to satisfy the patient. The healthcare provider should be able to measure the level of performance and the level of importance in order to service efficiency.Method: The research used quantitative method with operational research design to measure importance level and performance of service attribute in poly Asma-Allergy Dr. Indrajana Clinic Jakarta. Level of importance and performance measured by Importance-Performance Analysis (IPA) method to 20 types of service attributes, Patient expectation describes Importance level, while patient satisfaction describes Performance level of service attribute.Results: The results showed that there are 10 types of service attributes that should be